Pengembangan Media Pembelajaran Berbasis Aplikasi Lectora Inspire Pada Mata Pelajaran IPS Kelas V Di SDN 197 Sapolohe Kecamatan Bontobahari Kabupaten Bulukumba - Ahmad Syawaluddin; Andi Makkasau; Ina Fitrayani Jamal (Universitas Negeri Makassar, 2019)
This study studies on the development of media-based learning applications Lectora inspire on class V IPS courses at SDN 197 Sapolohe, Bontobahari Sub-district, Bulukumba district. The purpose of the research is to describe (1) The initial overview of the media needs of the application-based Lectora inspire in IPS class V subjects; (2) Overview of the results of the development of media-based learning application Lectora inspire on the subject of IPS class V, and (3) the level of media feasibility learning application-based Lectora inspire on the subjects of IPS class V at SDN 197 Sapolohe subdistrict Bontobahari, Bulukumba regency. This research approach is research and development, with the Borg & Gall development model. The process of development of media-based learning application Lectora Inspire on IPS subjects through 8 stages, namely research introduction and data collection, planning, product development, validity test (expert test), revision I, test small group, Revision II, and final product. Data collection techniques using poll instruments. Analysis of the data used is quantitative descriptive data analysis. The level of media feasibility learning application Lectora Inspire on IPS subjects based on a material expert assessment of 4.35, a media expert of 3.8, a teaching practitioner (teacher) of 4.55 and a student of 4.54 that gained an average A score of 4.31 with a very good category that shows the results that the learning media is worthy to be used in the learning process for students of class V SDN 197 Sapolohe, Bontobahari Sub-district, Bulukumba Regency.